Fostering prevention and care delivery services capability on HIV pandemic and Ebola outbreak symbiosis in Africa - Tambo, Ernest; Yah, Clarence S; Ugwu, Chidiebere E; Olalubi, Oluwasogo A; Wurie, Isatta; Jonhson, Jeannetta K; Ngogang, Jeanne Y (The Journal of Infection in Developing Countries, 2016)
Human immunodeficiency virus (HIV) and the re-emerging Ebola virus disease (EVD) are closely intertwined and remain a persistent public health threat and global challenge. Their origin and rapid transmission and spread have similar boundaries and share overlapping impact characteristics, including related symptoms and other interactions. The controversies and global threat of these viruses require rapid response policy and evidence-based implementation findings. The constraints and dual burden inflicted by Ebola and HIV infections are highly characterized by similar socio-demographics, socio-economic and political factors. EVD has similar effects and burdens to HIV infection. This study seeks to understand EVD in the context of HIV epidemic despite the challenges in developing an effective vaccine against HIV and EVD. Our findings show that early understanding, prevention and treatment of these diseases a global health threat mainly in Africa is important and valuable. The lessons learned so far from HIV and Ebola epidemics are crucial in health programming and execution of rapid response interventions and continued vigilance against EVD before it become another worldwide health menace. Therefore, the current regional West Africa EVD requires strengthening healthcare systems and building preparedness and response capacity. Importantly, appropriate community participation, health education and resilience coupled with deployment of effective novel diagnostic approaches in early warning and surveillance of threats and emerging diseases. Therefore, there is an urgent need to develop novel key strategies are crucial in curbing the constant viral resurgence, persistence transmission dynamics and spread, as well in accelerating Ebola vaccines regimen (immunization) development and national implementation plans in achieving sustained control, and eventual elimination.